Identification and frequency of transposable elements in Eucalyptus - Bacci Jr., Maurício [UNESP] (2005)
Transposable elements (TE) are major components of eukaryotic genomes and involved in cell regulation and organism evolution. We have analyzed 123,889 expressed sequence tags of the Eucalyptus Genome Project database and found 124 sequences representing 76 TE in 9 groups, of which copia, MuDR and FAR1 groups were the most abundant. The low amount of sequences of TE may reflect the high efficiency of repression of these elements, a process that is called TE silencing. Frequency of groups of TE in Eucalyptus libraries which were prepared with different tissues or physiologic conditions from seedlings or adult plants indicated that developing plants experience the expression of a much wider spectrum of TE groups than that seen in adult plants. These are preliminary results that identify the most relevant TE groups involved with Eucalyptus development, which is important for industrial wood production. Copyright by the Brazilian Society of Genetics.